PENGARUH TRADE-OFF NILAI TIME INVERSION TERHADAP OPTIMALISASI KUALITAS CITRA MRI LUMBOSACRAL SEKUEN STIR- SENSE CORONAL - Putu Sastra Andriani; I Putu Eka Juliantara; Ni Luh Putu Sari Widari; Nyoman Supriyani (JRI (Jurnal Radiografer Indonesia), 2022)
ABSTRAK Background :STIR is a fat suppression technique used in spinal MRI. The TI setting determines how much fat signaling will be suppressed. SENSE is a technique to reduce length of STIR examination time. According to Westbrook, the TI values for a 1.5 Tesla MRI 100 – 175 ms. To find the optimal TI for Lumbosacral MRI need to do a trade-off and research. Method :This research is quantitative with an experimental approach. The study used 15 samples were scanned 3 times on the STIR-SENSE Coronal sequence with TI variations 140, 150 and 160 ms. The data obtained then ROI and SNR is calculated using SPSS. Recorded the scan time. Results : Normality test, p value > 0.05 so the data distribution is normal. In the Test Of Within Subject Effect and the Test Of Between Subject Effect the value of Sig. <0.05 means there is an effect between variables. In the Pairwise Comparison test SNR significance value obtained on all data <0.05, it can be concluded there is a significant difference between the sequences. Scan time on trade-off TI of 140 and 150 ms is 2 minutes 36 seconds and on TI 160 ms 3 minutes 54 seconds. Conclusion :There is effect trade-of f TI value for optimizing the image quality of MRI Lumbosacral STIR-SENSE Coronal Sequence at Bali Mandara Hospital. The most optimal image quality ontime inversion trade-off 150 ms with mean 391.607 and a short examination time of 2 minutes 36 seconds.